Why Should Poor People Get Free Lawyers? - Webb, Duncan (Victoria University of Wellington Law Review, 1998)
Many view pro bono work as charity and those who engage in it as somewhat saintly. In this article Duncan Webb argues that there is an ethical obligation on all practitioners to devote some of their time to pro bono work. In making this argument he distinguishes pro bono work from other free work such as public interest, self promotional, and contingency fee work. He also attempts to address some of the objections that are commonly raised against a claim that pro bono work is ethically obligatory. He concludes by suggesting ways in which pro bono work could be most effectively delivered.